A study on HIV and hepatitis C virus among commercial sex workers in Tallinn. Issue 3 (6th February 2008) - Uusküla, A; Fischer, K; Raudne, R; Kilgi, H; Krylov, R; Salminen, M; Brummer-Korvenkontio, H; Lawrence, J St; Aral, S
Abstract : Introduction: Estonia is confronted by a dramatic expansion of the initially injection drug use-driven HIV epidemic. Little is known about HIV occurrence in population groups at high risk other than injection drug users. Objective: To obtain data on the prevalence of HIV and hepatitis C virus (HCV) among female sex workers (FSW) in Tallinn. Design: An unlinked, anonymous, cross-sectional survey of FSW recruited in Tallinn from October 2005 to May 2006. Methods: 227 FSW were recruited for the survey and biological sample collection (HIV, HCV antibodies detection) using a combination of time-location, community and respondent-driven sampling. Results: Among 227 women the HIV and HCV prevalences were 7.6% (95% CI 4.6% to 12.5%) and 7.9% (95% CI 4.5% to 12.6%), respectively. HIV prevalence was higher among FSW working in the street (odds ratio (OR) 6.4; 95% CI 1.1 to 35.6) and at the brothels and apartments supervised by the organised sex industry (OR 5.0; 95% CI 1.3 to 18.4). The duration of sex work was negatively associated with HIV prevalence (OR 0.78; 95% CI 0.63 to 0.97). Conclusions: Prevention needs of FSW in this area include increasing rates of HIV testing and putting in place effective programmes that can help extend HIV prevention behaviours across a range of sexual and drug use risk behaviours.